The mediating role of entrepreneurial orientation: the impact of entrepreneurship education and patriarchal culture on entrepreneurial intention among Indonesian university students - Saidun Hutasuhut; Reza Aditia; Thamrin (Cogent Business & Management, 2024)
This study explores the impact of entrepreneurship education on entrepreneurial orientation and intention among Indonesian students, while considering the influence of patriarchal culture. A quantitative research design using online surveys was employed, with 248 respondents who completed the entrepreneurship course in the even semester of 2022 at the Faculty of Economics, Universitas Negeri Medan. The surveys were administered online by the researchers. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized for analyzing the variables, and Mann–Whitney tests assessed gender and educational background differences. Results reveal a positive and significant effect of entrepreneurship education on both entrepreneurial orientation and intention. Entrepreneurial orientation significantly influences entrepreneurial intention. Surprisingly, patriarchal culture does not negatively impact entrepreneurial orientation or intention; its effect differs from expectations. No significant differences were found between genders or educational backgrounds regarding the impact of entrepreneurship education, orientation and intention. Specifically, no significant differences were found in the impact of entrepreneurship education, orientation and intention between genders or educational backgrounds. Also, entrepreneurial orientation partially mediates the relationship between entrepreneurship education and entrepreneurial intention.
Keywords: 650; entrepreneurship education; entrepreneurial orientation; patriarchal culture; entrepreneurial intentions; PlS-SEM